Impact of Arterial Remodeling of Intermediate Coronary Lesions on Long-Term Clinical Outcomes in Patients with Stable Coronary Artery Disease: An Intravascular Ultrasound Study - Liang Geng; Peizhao Du; Yuan Yuan; Liming Gao; Yunkai Wang; Jiming Li; Qi Zhang (Journal of Interventional Cardiology)
Background. Treatment of coronary intermediate lesions remains a controversy, and the role of arterial remodeling patterns determined by intravascular ultrasound in intermediate lesion is still not well known. The aim of this study was to investigate the impact of arterial remodeling of intermediate coronary lesions on long-term clinical outcomes. Methods. Arterial remodeling patterns were assessed in 212 deferred intermediate lesions from 162 patients after IVUS examination. Negative, intermediate, and positive remodeling was defined as a remodeling index of <0.88, 0.88∼1.0, and >1.0, respectively. The primary endpoint was the composite vessel-oriented clinical events, defined as the composition of target vessel-related cardiac death, target vessel-related myocardial infarction, and target vessel revascularization. Quantitative flow ratio was assessed for evaluating the functional significance of intermediate lesions. Results. 72 intermediate remodeling lesions were present in 66 patients, whereas 77 negative remodeling lesions were present in 71 patients, and 63 positive remodeling lesions were present in 55 patients. Negative remodeling lesions had the smallest minimum lumen area (4.16 ± 1.03 mm2 vs. 5.05 ± 1.39 mm2 vs. 4.85 ± 1.76 mm2; P<0.01), smallest plaque burden (63.45 ± 6.13% vs. 66.12 ± 6.82% vs. 71.17 ± 6.45%; P<0.01), and highest area stenosis rate (59.32% ± 10.15% vs. 54.61% ± 9.09% vs. 51.67% ± 12.96%; P<0.01). No significant difference was found in terms of quantitative flow ratio among three groups. At 5 years follow-up, negative remodeling lesions had a higher rate of composite vessel-oriented clinical event (14.3%), compared to intermediate (1.4%, P=0.004) or positive remodeling lesions (4.8%, P=0.06). After adjusting for multiple covariates, negative remodeling remained an independent determinant for vessel-oriented clinical event (HR: 4.849, 95% CI 1.542–15.251, P=0.007). Conclusion. IVUS-derived negative remodeling is associated with adverse long-term clinical outcome in stable patients with intermediate coronary artery stenosis.